2012
DOI: 10.1088/1674-1137/36/9/014
|View full text |Cite
|
Sign up to set email alerts
|

A positron source using an axially oriented crystal associated to a granular amorphous converter

Abstract: A non-conventional positron source using the intense γ radiation from an axially oriented monocrystal which materializes into e+e− pairs in a granular amorphous converter is described. The enhancement of photon radiation by multi-GeV electrons crossing a tungsten crystal along its <111> axis is reported. The resulting enhancement of pair production in an amorphous converter placed 2 meters downstream, is also reported. Sweeping off the charged particles from the crystal by a bending magnet upstream of the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this approach, a bending magnet can be installed between the radiator and the target-converter, which allows sweeping off the charged particles emerging from the crystal (Chehab-Strakhovenko-Variola scheme), hence reducing the thermal and radiation load being of great importance for the linear collider projects. Moreover, a new option of the target-converter can be also considered implying the use of a granular target made of small spheres providing better heat dissipation and better resistance to thermal shocks [99]. The hybrid scheme, thus, has been adopted by CLIC as a baseline for the unpolarized positron source.…”
Section: Jinst 17 P05015mentioning
confidence: 99%
“…In this approach, a bending magnet can be installed between the radiator and the target-converter, which allows sweeping off the charged particles emerging from the crystal (Chehab-Strakhovenko-Variola scheme), hence reducing the thermal and radiation load being of great importance for the linear collider projects. Moreover, a new option of the target-converter can be also considered implying the use of a granular target made of small spheres providing better heat dissipation and better resistance to thermal shocks [99]. The hybrid scheme, thus, has been adopted by CLIC as a baseline for the unpolarized positron source.…”
Section: Jinst 17 P05015mentioning
confidence: 99%
“…For the latter the Peak Energy Deposition Density (PEDD) is a critical parameter. In [6] the authors, using the experience of the target for muon collider, shown that using a granular target instead of compact reduces the PEDD (Table 2). The high ratio of surface volume of the spheres (3/r) makes easier the thermal dissipation.…”
Section: Converter Study : Granular Amorphous Targetmentioning
confidence: 99%
“…Crystal-based solutions [47] are also under consideration for the slow extraction of circulating beams in the Super Proton Synchrotron (SPS) at CERN [48] or at synchrotron facilities [49]. Aside from particle beam steering, crystals could also be used as innovative elements for generation of hard radiation [50,51] or positron [52] beams and for the realization of compact photo-converter [8] and forward electromagnetic calorimeters [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to traditional magnetic optical elements used in accelerators, crystals operate without the need of a power source, generally do not require a cryogenic environment, and are extremely compact and light-weight, typically less than 1 Kg, making them appealing for integration in particle accelerators. The use of crystals have been suggested also for the Future Circular Collider (FCC) [39,41,[55][56][57], the International Linear Collider (ILC) [52,58], the Compact Linear Collider (CLIC) [58,59], and the Circular Electron Positron Collider (CEPC) [60] and it could be exploited in a future muon collider design [61,62]. Given the extremely high intensity and energy reached in modern and future particle accelerators such as the HL-LHC or in future planned ones, the implementation of bent crystals at these facilities demands facing various technological challenges and a considerable improvement of the state-of-the-art in the manufacturing of crystals for scientific or technological application.…”
Section: Introductionmentioning
confidence: 99%